Shooting Success Level in Basketball Seen from The Formation of The Throwing Angle - Fitra Faradisha Putri; Iman Imanudin; Mohammad Zaky (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study focuses on analyzing the relationship between the release angle and the success rate of shooting in the free throw technique in basketball. The study was conducted on members of the Mitra Satu Basketball club using a quantitative descriptive approach. A total of 10 players performed 10 free throw attempts, resulting in a total of 100 shooting data that were analyzed using Kinovea software to measure the release angle, and the chi-square test to determine the relationship between the angle and the success rate of the shot. The results of the analysis showed that there was a significant relationship between the range of the release angle and the success rate of shooting (p = 0.009). The angle range of 40–49 degrees produced the highest success rate, which was 48.4%, compared to other angle ranges. This study confirms that the release angle plays an important role in determining shooting accuracy, and certain angles can provide biomechanical advantages for players. Thus, coaches and athletes are advised to focus shooting training on achieving optimal angles and utilizing movement analysis to improve technique consistency. This study also opens up opportunities for further research involving a larger sample size and additional variables, such as throwing distance, which was not examined in this study but could significantly contribute to a deeper understanding of shooting performance in basketball.